‘Relocating’ Adolescents from Risk beyond the Home: What Do We Learn When We Ask about Safety? - Wroe, Lauren Elizabeth; Peace, Delphine; Firmin, Carlene (The British Journal of Social Work, 2023)
There is an absence of evidence supporting the use of ‘out-of-area placements’ to address risks adolescents face beyond the home. Approximately one in ten adolescents in England and Wales are ‘relocated’ from their hometowns by children’s social care teams due to these risks. Initial findings from the Independent Review of Children’s Social Care in England situate these relocations as a ‘failure’ to safeguard teenagers. Using participatory approaches to research design and data collection, this article asks what do we learn about the impact of relocations when we ask about safety? Activity-based, qualitative interviews were conducted with young people (n = 5), parents (n = 3) and professionals (n = 15) based in England and Scotland between 2020 and 2021, asking what worked and what didn’t when a relocation was chosen, and what was the perceived impact on safety. Interview data were thematically analysed in collaboration with young people and a Research Advisory Group of professionals, all with expertise in the area. Data indicated a tension between what professionals, and then parents and young people, thought was significant when planning relocations and an ambivalence about the impact of relocations. Considerations for safety planning are suggested to support young people’s holistic safety needs.
EPrint Processing Status: Full text deposited in DRO